ILAM recording tour (South West Africa and north-western Cape) - Tracey, Hugh (International Library of African Music, 1965)
Two features of the music were remarkable. The few Herero items were immediately recognisable as being similar to the music of the Hima people of the great lakes region, more particularly to the Haya of Bukoba on the south-west corner of Lake Victoria. The Ovambo music in many instances could hardly be distinguished from Luvale music originating some 300 or more miles to the north-east on the southern Congo border. A linguist, Dr. Ernst Westfall, of Cape Town University whom I consulted, maintained that there had been a connection between the two people some 300 years ago, but that they had had no recent contact. The Herero are popularly believed to have come from the Hima group several centuries ago, and the coincidence of similar musical styles would seem to support this evidence.
Keywords: African Music; Republic of the Congo (Léopoldville)